Application of Fullerenes as Photosensitizers for Antimicrobial Photodynamic Inactivation: A Review - Hou, Wenjia; Shi, Guorui; Wu, Songze; Mo, Jiayi; Shen, Lan; Zhang, Xiuqiang; Zhu, Yabin (Frontiers in Microbiology, 2022)
Antimicrobial photodynamic inactivation (aPDI) is a newly emerged treatment approach that can effectively address the issue of multidrug resistance resulted from the overuse of antibiotics. Fullerenes can be used as promising photosensitizers (PS) for aPDI due to the advantages of high triplet state yields, good photostability, wide antibacterial spectrum and permissibility of versatile functionalization. This review introduces the photodynamic activities of fullerenes and the up-to-date understanding of the antibacterial mechanisms of fullerene-based aPDI. The most recent works on the functionalization of fullerenes and application of fullerene derivatives as PS for aPDI are also summarized. Finally, certain remaining challenges are emphasized to provide guidance on future research directions for achieving clinical application of fullerene-based aPDI.